Towards Cyber City: DKI Jakarta and Surabaya Provincial Government Digital Public Services - Angeline, Mia; Evelina, Lidia; Siregar, Vini Mariani (Bina Nusantara University, 2016)
The goal of this research was to do a comparative study on the use of information technology in DKI Jakarta Provincial Government through Jakarta.go.id website and Surabaya City Local Government through Surabaya.go.id website. This research focused on public services and interactive use of communication media. Research method used was descriptive qualitative. Data were collected through a depth interview with Jakarta.go.id and Surabaya.go.id website administrators, observation of digital data, literature review, and through secondary data. Data analysis was done through a constant comparative technique. The results indicates that diffusion innovation theory is used by provincial government to give digital public services. It means that the government is seeking people to adopt the use of information technology in the interaction with the government. Local and Provincial Government provides a media center for public services, which the public can access information and provide input to the government. Some of the challenges show that society is not fully ready to change from conventional public services to digital public services received from the government. There is a massive need to educate society while also providing free mobile internet services. Other than that, there is also a gap in internal governmental human resources skill and competences. As a solution to some of these problems, both DKI Jakarta and Surabaya Provincial Government need to apply information technology to achieve e-government and cyber city.